2016
DOI: 10.18632/aging.101024
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenolic drug composition based on benzenepolycarboxylic acids (BP-C3) increases life span and inhibits spontaneous tumorigenesis in female SHR mice

Abstract: Effects of long-term application of novel polyphenolic composition BP-C3, containing polyphenolic benzenepolycarboxylic acids, vitamins and minerals on some biomarkers of aging, life span and spontaneous tumorigenesis has been studied in female SHR mice. Administration of BP-C3 with drinking water (0.005%) did not exert any toxic effect (did not have effect on general condition of animals, weight dynamics and consumption of food), postponed age-related switch-off of estrous function, caused slight reduction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 39 publications
(32 reference statements)
0
9
0
Order By: Relevance
“…Investigational medicinal product, BP-C2, a composition of BP-Cx-1 with ammonium molybdate, inhibits radiation-induced skin damage in mice (13) and improves quality of life of patients with cancer treated with 5-FU-containing regimens (14). BP-C3, used in the present study, was previously demonstrated to exhibit geroprotective activity (15).…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Investigational medicinal product, BP-C2, a composition of BP-Cx-1 with ammonium molybdate, inhibits radiation-induced skin damage in mice (13) and improves quality of life of patients with cancer treated with 5-FU-containing regimens (14). BP-C3, used in the present study, was previously demonstrated to exhibit geroprotective activity (15).…”
Section: Introductionmentioning
confidence: 84%
“…The results of previous study on BP-C2, administered from week 2-26 in combination with a FOLFIRINOX regimen in a patient with inoperable pancreatic cancer, indicated that during treatment no neutropenia developed for 18 weeks, and blood biochemistry normalised by week 25 (14). In a long-term study performed in female SHR mice, the mean life span increased by ~50 days in animals treated with BP-C3 compared with the untreated control group (15). A greater number of tumour-free mice and delayed age-related switch-off of the oestrus function were observed, possibly due to immunomodulatory effect of BP-C3 (15).…”
Section: A Spleenmentioning
confidence: 98%
See 1 more Smart Citation
“…BP-C3 is a composition of BP-Cx-1 with iron complex, selenium, ascorbic acid, and retinol. It exhibits geroprotective activity [ 19 ] and reduces 5-fluorouracil toxicity in mice by accelerating recovery of leukopoiesis and protecting small intestine epithelium [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…BP-C3 is a formulation, which comprises BP-Cx-1 with iron complex, selenium, ascorbic acid and retinol. Longterm treatment with BP-C3 had anticarcinogenic and geroprotective activity in female SHR mice [2]. BP-C3 was found to reduce the toxic effect of 5-fluorouracil against hematopoiesis and intestinal epithelium which was evident by preserved organ/body ratios for the lymphopoietic organs, anemia reduction and intestinal crypt survival [3].…”
mentioning
confidence: 99%